2021
DOI: 10.3390/su13158258
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Pre-Harvest Organic Cytokinin Application on the Post-Harvest Physiology of Pepper (Capsicum annuum L.)

Abstract: Peppers are cultivated in almost all provinces in Turkey, making up approximately 7% of the world’s production. In this study, the effects of pre-harvest cytokinin application on the postharvest physiology of pepper (Capsicum annuum L.) fruits (cv. Akra and Melek F1) grown in ecological conditions in Turkey (Van, eastern Turkey) were investigated. During the growing period, organic cytokinin(nytrozine) at two concentrations (50 and 100 ppm doses) was applied by spraying. Peppers were harvested in green maturit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(2 citation statements)
references
References 57 publications
0
2
0
Order By: Relevance
“…Cytokinins can prevent the degradation of proteins due to their effects on tRNA in the cell [25,26]. It has been reported by different researchers that postharvest cytokinin treatments gave positive results in broccoli [26,27], and cauliflower [28].…”
Section: Introductionmentioning
confidence: 99%
“…Cytokinins can prevent the degradation of proteins due to their effects on tRNA in the cell [25,26]. It has been reported by different researchers that postharvest cytokinin treatments gave positive results in broccoli [26,27], and cauliflower [28].…”
Section: Introductionmentioning
confidence: 99%
“…The enzymatic antioxidant system composed of antioxidant enzymes such as SOD, CAT, POD, and APX is one of the main ways to maintain the dynamic balance of ROS in fruit. SOD defends against ROS damage by converting O 2 − to H 2 O 2 [41,44]. The experimental results showed that the SOD activity of M2 treatment in the peel and pulp was higher than that of other treatments and controls during the storage period.…”
Section: Discussionmentioning
confidence: 93%